An Online Compression Algorithm for Positioning Data Acquisition (Informatica, 2014)
Positioning data are usually acquired periodically and uploaded to the server via wireless network inthe location data acquisition systems. Huge communication overheads between the terminal and theserver and heavy loads of storage space are needed when a large number of data points are uploaded.To this end, an online compression algorithm for positioning data acquisition is proposed, whichcompresses data by reducing the number of uploaded positioning points. Error threshold can be setaccording to users' needs. Feature points are extracted to upload real-timely by considering thechanges of direction and speed. If necessary, an approximation trajectory can be obtained by using theproposed recovery algorithm based on the feature points on the server. Positioning data in threedifferent travel modes, including walk, non-walk and mixed mode, are acquired to validate the efficiencyof the algorithm. The experimental results show that the proposed algorithm can get appropriatecompression rate in various road conditions and travel modes, and has better adaptability.